Maqashid Syariah Review of Inheritance Distribution Practices from Parents to Children in the Betawi Indigenous Community of Kapuk Village: A Socio-Legal Empirical Study - Diva Hardiyanti Abdillah; Muhammad Yusron (Sahaja: Journal Sharia and Humanities, 2025)
This study examines the inheritance distribution practices among the Betawi indigenous community in Kapuk Village, Cengkareng District, West Jakarta, through the theoretical lens of maqashid al-syariah as articulated by Muhammad al-Tahir ibn Asyur. Employing an empirical legal research design with a socio-legal approach, data were collected through semi-structured interviews with five families of testators and heirs, community leaders, and complemented by secondary sources, including Islamic jurisprudence literature and customary law documents. The findings reveal that inheritance distribution in this community predominantly occurs during the parents’ lifetimes through inter vivos transfers (hibah), deviating from the classical faraid system. Parents allocate property based on subjective criteria such as emotional proximity, filial responsibility in eldercare, and residential proximity rather than the Quranic proportional shares. While this practice reflects deeply embedded Betawi cultural values of family-centrism (kekeluargaan) and social harmony (keselametan), it frequently generates latent disputes due to the absence of formal documentation and witnesses. Nevertheless, through the analytical framework of maqashid al-syariah, this study argues that such practices align with the higher objectives of Islamic law, particularly the principles of maslahah (public benefit), al-musawah (substantive equality), sadd al-dzariah (prevention of harm), and social stability. This study contributes to the discourse on legal pluralism in Muslim-majority societies by demonstrating how indigenous communities negotiate between customary practices and Islamic legal norms through contextual ijtihad.